Hubungan Riwayat Pola Mengonsumsi Susu Botol dengan Tingkat Keparahan Early Childhood Caries (ECC) pada Anak Usia 3-5 tahun di Kecamatan Kuranji Kota Padang - Annissa Achmadsyah Gewang; Deli Mona; Arymbi Pujiastuty (Andalas Dental Journal, 2021)
Early Childhood Caries (ECC) is a state of occurrence of decayed (cavities and non cavities), missing (due to caries), or filling on one or more deciduous teeth in children aged ≤ 71 months. Wayne (1999) divided the severity of ECC into three classifications based on clinical signs, causes, and age of the child namely type I (mild), type II (moderate), and type III (severe). The rate of caries incidence is increasing in children who consume milk using bottles. Clinical pattern to ECC caused by bottle feeding has a distinctive pattern, which is about four upper incisors, while four lower incisors usually remain healthy. This study aims to determine the correlation between the history and pattern of bottle feeding and the severity of ECC in children aged 3-5 years in Kuranji District, Padang City. This study is an analytical study with a cross sectional approach. The study sample consisted of 58 children aged 3-5 years with a history of bottle feeding for at least two years. Samples are selected through consecutive sampling technique. Data are collected using questionnaires and through examining respondents' oral cavity. Data collected are analyzed using Chi-Square Test. Statistical test result shown p < 0,15 for each pattern of bottle feeding duration in years, the time of bottle feeding, the addition of sweeteners, and preventive measures. P is valued as > 0,15 for bottle feeding method. There is a significant relationship between the history and the pattern of bottle feeding duration in years, the time of bottle feeding, the addition of sweeteners, and preventive measures with the severity of ECC in children aged 3-5 years in Kuranji District, Padang City.